Agribisnis Pepaya Mojosongo (MJ 9) Sebagai Komoditas Unggulan Daerah Di Kabupaten Boyolali - Edi Paryanto; Sudiyarto Sudiyarto; Sumartono Sumartono (Forum Agribisnis, 2022)
Papaya Mojosongo (MJ 9) is one of the main fruit commodities in Boyolali Regency. This research aimed to analyze the potential of Mojosongo (MJ 9) papaya as a superior commodity in Boyolali Regency. To this end, this study applied a descriptive qualitative and quantitative methods by using a case study. In this reseacrh, 25 key informants were involved in in-depth interviews and FGDs. The analytical methods used were 1) Location Quotient (LQ) analysis, 2) Business Feasibility Analysis and 3) descriptive analysis of papaya agribusiness potential from various aspects. The results showed that the potential for developing Mojosongo papaya (MJ 9) agribusiness is quite significant and it is feasible to be developed as a leading commodity in Boyolali Regency. This is due to several reasons. 1) the LQ values of papaya agribusiness in 2019 and 2020 were 5,83 and 4,03. An LQ value of more than 1 indicates that the commodity is a regional superior commodity. 2) The results of the R/C ratio analysis were 1,79; with NPV value of Rp 5,706,633 and IRR value of 145,39% per year. An interest rate higher than 20% per year indicates that MJ9 papaya agribusiness is efficient and profitable. 3) The potential for the development of Papaya Mojosongo Agribusiness (MJ 9) is significantly promising because it absorbs a lot of labor and contributes to the economy. This business is also a basic economic sector, a sustainable and renewable business that does not conflict with social and cultural norms. Moreover, this agribusiness has a high absorption capacity due to its large market. The results of this research can serve as a reference for policy making strategies in developing MJ 9 papaya agribusiness in Boyolali today and and in the future.